Real world research : a resource for users of social research methods in applied settings - Robson, Colin (Wiley-Blackwell, 2011)
"Given the positive nature of the review feedback, and following the basic 'if it ain't broke ...' principle, I propose to retain the same concept of a broadly-based text with an even-handed coverage of qualitative and quantitative approaches as in previous editions. There will be a continuing focus on what I have termed 'Real World Research' and an intention for it to serve as a resource for those planning to carry